Researching the aptitude of young volleyball players (children and adolescents) - Biróné Ilics, K.; Baloghné Bakk, A.; Suskovics, C. (Journal of Human Sport & Exercise, 2013)
In order to establish a child`s calculated performance in a selected branch of sport we need to clarify if he or she has the external and internal conditions with which he or she can be competitive. In our research the target age group of boys and girls are teenagers (13-16 year-olds) (N= 124). This research has a wide range of aspects; it covers anthropometrical measurements, general motor testing, parental and players` questionnaires. Our aim is to determine the player`s aptitude for high performance. Based on the listed literature the right person is whose height at women is 175-195cm, at men is 185-210cm; moreover his or her motor skill standards are far better than the peers or the individual has favorable parental, environmental or any other kind of condition.